Internalisasi Nilai Etika Hindu Terhadap Sopan Santun Siswa Sekolah Dasar Di Era Digital - Mertayasa, Ketut; Agusvina, Rinda; Mudiyanti, Ni Nyoman; Mariyati, Ketut (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2025)
The degradation of ethics and politeness among elementary school students has become increasingly concerning, particularly due to uncontrolled use of social media. This study aims to formulate strategies for internalizing Hindu ethical values to foster politeness in students in the digital era. The research employed a literature review method with an integrative analysis approach, linking Hindu ethical teachings to character education. The findings reveal that the values of Dharma, Ahimsa, Satya, and Tri Kaya Parisudha are highly relevant in guiding students to interact ethically and responsibly in digital environments. Successful implementation requires active involvement from teachers as moral role models and from families in supervising and limiting access to social media. Schools can leverage technology as an ethical education tool through clear regulations, preventing students from accessing inappropriate content and enabling them to maintain politeness in communication. Synergy between schools and families is essential to ensure the successful cultivation of student ethics in the digital age.